The last lecture [compact disc, unabridged] - Pausch, Randy (Hyperion Audiobooks, 2008)
"A lot of professors give talks titled "The Last Lecture." While they speak, audiences can't help but mull the same question: What would we want as our legacy? When Randy Pausch, a computer science professor at Carnegie Mellon, was asked to give such a lecture, he didn't have to imagine it as his last, since he had recently been diagnosed with terminal cancer. But the lecture he gave--"Really Achieving Your Childhood Dreams"--wasn't about dying. It was about overcoming obstacles, enabling the dreams of others, of seizing every moment. It was about living"--Container.